2018
DOI: 10.1016/j.mpmed.2018.06.009
|View full text |Cite
|
Sign up to set email alerts
|

Hypertension

Abstract: Hypertension has high prevalence in the general population, accounts for one in every eight consultations in primary care and is a major risk factor for cardiovascular and renal disease. Despite the wide availability of suitable medicines, only about 25% of all hypertensive patients have their blood pressure controlled adequately. Effective management of patients with hypertension mandates assessment for asymptomatic target organ damage and also for potential secondary causes. Accurate blood pressure measureme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 8 publications
1
6
0
3
Order By: Relevance
“…First, over a 7-year period, the probability of progressing from normal/elevated BP to an adjacent state, that is, stage 1 hypertension was 19%, greater than progressing to a non-adjacent state, stage 2 hypertension which was 16.9%. Since an individual can be at a single state at a particular time point ( 24 ), the probabilities for stage 1 and stage 2 hypertension are indicative of the high risk of potential disease outcomes and the consistency of our findings with more recent studies showing an increase in the prevalence of hypertension ( 34 ).…”
Section: Discussionsupporting
confidence: 85%
“…First, over a 7-year period, the probability of progressing from normal/elevated BP to an adjacent state, that is, stage 1 hypertension was 19%, greater than progressing to a non-adjacent state, stage 2 hypertension which was 16.9%. Since an individual can be at a single state at a particular time point ( 24 ), the probabilities for stage 1 and stage 2 hypertension are indicative of the high risk of potential disease outcomes and the consistency of our findings with more recent studies showing an increase in the prevalence of hypertension ( 34 ).…”
Section: Discussionsupporting
confidence: 85%
“…[8,9] Hypertension is the largest risk factor associated with mortality worldwide. [10] Therefore, a medication can effectively reduce blood pressure, but synthetic antihypertensive drugs can lead to serious adverse side effects. The widely used are angiotensin converting enzyme (ACE) inhibitors, an enzyme widely distributed, zinc-dependent metallopeptidase that converts angiotensin I to angiotensin II.…”
Section: Introductionmentioning
confidence: 99%
“…Hypertension is the largest risk factor associated with mortality worldwide [10] . Therefore, a medication can effectively reduce blood pressure, but synthetic antihypertensive drugs can lead to serious adverse side effects.…”
Section: Introductionmentioning
confidence: 99%
“…Hypertension is very important health problem causing death around the World, and it is associated with coronary diseases [1]. Pathogenesis of this disease has indicated that the angiotensin-converting enzyme (ACE) is a powerful regulator for the balance of blood pressure [2].…”
Section: Introductionmentioning
confidence: 99%